First-in-Human Phase I Clinical Trial of the Adenosine A1R/A3R Agonist AST-004 in Healthy Subjects - Manna, Lisa M; Hernandez, Juan; Hunt, Dawn E; Lakner, Géza; Matson, Mark A; Poe, Russell B; Korinek, William S; Lancey, Robert A; Liston, Theodore E (Stroke (1970), 2024)
AST-004 is a small-molecule adenosine A1/A3 receptor agonist that has exhibited significant cerebroprotective efficacy in preclinical models of acute ischemic stroke and traumatic brain injury. The primary objectives of this clinical phase I first-in-human study were to evaluate the safety and tolerability profile of single ascending intravenous doses in healthy subjects. The secondary objectives were to characterize the single-dose pharmacokinetic profiles in plasma, cerebrospinal fluid (CSF), and urine. In part 1 of the study, AST-004 was administered in ascending dose cohorts of 5, 25, 50, 75, and 100 mg, with 6 subjects in each cohort receiving the study drug and 2 receiving placebo. In part 2, all 12 subjects received a 100 mg IV infusion of the study drug followed by a single CSF collection per subject via lumbar puncture at 20, 40, or 60 minutes after infusion. A total of 42 subjects received AST-004, with no severe or serious adverse events observed. Twelve of these subjects experienced a treatment-emergent adverse event, the most frequent across groups being headache. In part 2, pharmacokinetic analyses confirmed that AST-004 was distributed in the CSF, with the CSF-to-plasma ratio increasing over the 3 timepoints sampled. The mean half-life was 1.1 to 1.4 hours for doses of 25 to 100 mg, and the geometric mean maximum plasma concentration obtained in the highest dosing cohort (100 mg) was 2232±428 ng/mL. AST-004 was safe and well-tolerated at plasma concentrations 3 to 8× higher than those associated with significant efficacy in astrocyte's preclinical primate stroke efficacy studies, with CSF concentrations highest at the 60-minute collection timepoint, the last timepoint tested. This study supports additional clinical investigations, including evaluation of an extended infusion to support the phase 2 program in stroke and traumatic brain injury.